Assessment of the Level of Automation and Utilization of Enterprise Resource Planning System – A Case Study of Kenya Medical Training College - Amdany, Sammy Sumukwo; Magangi, Douglas Bundi; Nyakango, Louise Nyaboke; Otwori, Victor Nyarango (International Journal of Research in Interdisciplinary Studies, 2023)
In the twenty-first century, Enterprise Resource Program (ERP) systems have become widely used as the preferred corporate management tools. They are essential in a number of roles, including project planning, administration, finance, human resources, and supply chain management. In order to better management and administration, academic institutions, including Kenya Medical Training College (KMTC), have begun to replace their outdated systems with ERP projects. This study attempted to evaluate the ERP system's installation at KMTC by evaluating the extent of automation in its various departments in improving efficient service delivery. A sample of 115 respondents were chosen using proportionate stratified sampling as part of a descriptive survey research methodology. Statistical analysis reveals that that most of the respondent with less than 50% reported little extent of automation of ERP system. However, the finance department had a large extent of automation as compared to other departments with 51.3%. Additionally, the extent of use of ERP for various functions recorded less than 30% overall in all the operations carried out by the College. In light of these findings, the study proposes stakeholders in KMTC to develop comprehensive ERP implementation plans incorporating change readiness assessments and robust training programs to boost user acceptance and competency.